EAPH-15. COMBINATION THERAPY WITH VINCRISTINE, IRINOTECAN, AND TEMOZOLOMIDE IN CENTRAL NERVOUS SYSTEM MALIGNANCIES. Issue 2 (22nd June 2018) - Gibson, Amber; Bavle, Abhishek; Gross, Naina; Gavula, Theresa; McNall, Rene
Abstract: Current therapeutic options for high grade gliomas including DIPG (HGG) and relapsed or refractory CNS malignancies (R-CNS), excluding low grade gliomas, are often of limited efficacy. We examined the combination of vincristine with extended dosing of irinotecan and temozolomide with an antibiotic for diarrhea prophylaxis (VITA) in a phase I study and have continued to use it after study closure. We often combine the regimen with radiation and/or bevacizumab. We treated 3 newly diagnosed HGG and 19 R-CNS patients with mild toxicity (see prior report). Here we report the efficacy. We conducted a retrospective chart review of pediatric patients treated with VITA to quantify the median time to progression (TTP) and median OS. Overall, the 22 patients had TTP of 8.25 (range 1.3 to >118 months) and OS 12 (range 3 to >118 months). By tumor type - medulloblastoma (8) 12 and 13.75 months, PNET (5) 20 and 27+ months (3 of 5 still alive), HGG (7) 5 and 7 months (8 and 12.5 months if newly diagnosed), primary CNS sarcoma (1 myxoid liposarcoma and 1 Ewing) 39 and 43 months. If radiation used in conjunction (8 patients), the outcomes improved with 20.5 months TTP and 36 months OS. Three are alive with no evidence of disease 27–118 months after VITA and radiation. These data suggest VITA can provide prolonged survival for many patients with challenging CNS malignancies but is rarely curative. We believe VITA is a promising backbone therapy on which to add novel therapies.